Media Pembelajaran Interaktif Mata Kuliah Pemrograman Web Berbasis Android - Abdullah, Alfiah; Achmad, Andani; Sahibu, Supriadi (STMIK AKBA, 2021)
The learning process faces relatively large challenges, which are related to the extraordinarydevelopments in science and technology (IPTEK). The rapid development of science andtechnology offers a variety of new facilities in learning, especially the variety of learning mediathat educators can use in delivering learning materials. Interactive learning media is alearning medium that is used in learning and there is good interaction between students andlecturers, students and students. Currently, the teaching and learning process uses the manualmethod, provided that lecturers and students come face to face in order to carry out theteaching and learning process. When lecturers cannot attend the learning process, thedistribution of knowledge will be hampered. Interactive learning media is an effective way tostimulate students. The purpose of this research is to design applications that can attract theattention of students and facilitate understanding of web programming materials. Datacollection methods used are observation and interviews. The research stages of data collectionare then the design of an Android-based interactive learning media application device. Theresults of the study can be concluded that the Interactive Learning media for studying web programming courses can attract students' attention and make it easier to understand webprogramming materials